Kajian Filsafat Progesivisme dalam Pendidikan - Sulistyaningsih, Dewi Ayu (Yayasan Sembilan Pemuda Indonesia, 2023)
Progressivism is a modern educational philosophy that calls for changes in the administration of education in order to progress. This flow of progressivism prioritizes the implementation of child-centered education in schools and limits teachers' activities only as mentors, supervisors and mentors for students. Progressivism advocates changes for the better that prioritize students and develop various student skills to realize learning. The educational curriculum prioritizes what students do, not what educators do. The goal of progressivism in education is to make educational practices that have previously seemed authoritarian become democratic and more respectful of children's potential and abilities, as well as encouraging more inclusive learning for students.